Non-invasive Estimation of Foliar Nitrogen Concentration Using Spectral Characteristics of Menthol Mint (Mentha arvensis L.) - Pandey, Praveen; Singh, Swati; Khan, Mohammad Saleem; Semwal, Manoj (Frontiers in Plant Science, 2022)
Menthol mint (Mentha arvensis L., Family: Lamiaceae), popularly known as Corn mint or Japanese mint is an important industrial crop widely grown for its valued essential oil. Nitrogen (N) is an important macro-nutrient, essential for optimizing the yield and quality of crops. Hence, rapid and accurate N estimation is crucial for nutrient diagnosis in plants to surge precision N fertilization. Usually, N concentration is estimated by destructive sampling methods; however, an indirect assessment may be possible based on spectral characteristics. This study aimed to correlate the foliar N concentration based on non-destructive (reflectance) and destructive (laboratory analyses) methods in menthol mint. Foliar N concentration was measured through the Kjeldahl method and reflectance by Miniature Leaf Spectrometer C-710 (CID Bio-Science). Using reflectance data several Vegetation Indices (VIs) viz., Normalized Difference Red Edge (NDRE), Red edge Normalized Difference Vegetation Index (reNDVI), Simple Ratio (SR), Green-Red Vegetation Index (GRVI), Canopy Chlorophyll Content Index (CCCI), Photochemical Reflectance Index (PRI), Green Chlorophyll Index (CIGreen), Red Edge Chlorophyll Index (CIRed Edge), Canopy Chlorophyll Index (CCI), Normalized Pigment Chlorophyll Ratio Index (NPCI) and Structure Insensitive Pigment Index (SIPI) were developed which were used to determine foliar N concentration. The highest correlation (r) between VIs and foliar N concentrations were achieved by NDRE (0.89) followed by reNDVI (0.84), SR (0.83), GRVI (0.78), and CCCI (0.76). Among the vegetation indices, NDRE index has been found to be the most precisely predicted foliar N concentration (R2 = 0.79, RMSE = 0.18). In summary, if there are any N deficiencies faced by the crop during its growth period, it can be detected by calculating NDRE as well as reNDVI, which can be used as an indicator for recommending precise nitrogenous fertilizers management.